Population dynamics of tundra voles in relation to configuration of willow thickets in southern arctic tundra - Henden, John-André; Ims, Rolf Anker; Yoccoz, Nigel; Sørensen, Raymond; Killengreen, Siw Turid (Polar Biology, 2011)
The areal extent and conWguration of thickets of willow shrubs are currently changing in the Arctic both as an eVect of global warming and changed browsing pressure of reindeer. These changes have been predicted to impact the distribution and abundance of wildlife species relying on willow thickets as habitat. We assessed the relation between variables quantifying willow thicket configuration and population dynamics of tundra voles (Microtus oeconomus) in three riparian regions in Finnmark, northern Norway, which were subject to intense browsing by semidomesticated reindeer. The tundra vole, which exhibits 5-year population cycles in Finnmark, is the dominant small rodent species in riparian landscape elements in southern arctic tundra. In the course of a 4-year trapping study, tundra vole populations went through the cyclic phases of increase, peak and crash, however, with distinct differences between the three regions in the population dynamics. Within regions, the occupancy pattern during the increase phase was positively related to willow thicket configuration (in particular edge density and willow height) only in the region attaining the highest abundance and occupancy. However, local abundance was not clearly related to habitat features within any regions. The lack of consistency in the response of tundra vole populations to willow thicket configuration, as well as the positive relation between the degree of thicket shredding and tundra vole habitat occupancy in one of the regions, indicates that tundra voles will not be much aVected by climate or browsing induced changes in the shrubbiness of the tundra in the future.